Implementation Analysis of the Marketing Mix Strategy for the Begos Restaurant, Makassar City - Gumelar, A.; Ridwan, M.; Hastang, H.; Bahtiar, B.; Windiana, W. (Hasanuddin Journal of Animal Science (HAJAS), 2025)
This study aims to analyze the implementation of the 7P marketing mix strategy (Product, Price, Place, Promotion, People, Process, Physical Evidence) at Bebek Goyang Sulawesi Restaurant in Makassar City. A descriptive research method with a qualitative approach was employed, where data were collected through interviews and questionnaires administered to management and consumers. The findings reveal that most marketing mix elements have been effectively implemented, particularly regarding product quality, strategic location, and digital media promotions. However, some areas require improvement, such as the pricing strategy, which is perceived as less competitive, and the cleanliness of physical facilities. From the consumers' perspective, the "People" and "Process" elements received high ratings, while the "Price" and "Physical Evidence" elements still need enhancement. This study provides recommendations to improve customer satisfaction through refining pricing strategies, enhancing cleanliness, and innovating promotional efforts. The findings are expected to serve as a reference for the management of Bebek Goyang Sulawesi Restaurant in optimizing its marketing strategy to achieve a competitive advantage in the increasingly competitive culinary industry. Keywords: Competitive advantage, consumer perspective, culinary industry, marketing mix implementation, strategic pricing